Editorial (International Journal of Business Innovation, 2024)
It is with great pleasure that we present the second issue of Volume 3 of the International Journal of Business Innovation. This issue once again reflects our commitment to publishing cutting-edge and high-quality research focused on critical topics shaping today’s business environment. The collaboration between authors, reviewers, and our editorial team continues to drive the success of this journal, ensuring both the relevance and quality of the articles presented.In this edition, we are excited to share a collection of articles addressing contemporary issues in areas such as gender representation, fiscal complexity, and investor decision-making. The diversity of themes covered in this issue highlights the complexity and dynamism of the business world, offering comprehensive insights valuable to both academia and industry professionals.The first article, "Female Under-Representation in Audit Profession and Leadership: A Study in the Portuguese Context" by Sílvia Bernardo, Isabel Pedrosa, and Daniela Monteiro, explores the under-representation of women in the audit profession in Portugal, particularly in leadership positions. This study delves into the historical and social barriers women face in advancing their careers and offers pathways to overcoming these challenges. Additionally, the paper contributes to the United Nations' Sustainable Development Goal 5 on gender equality, providing a significant contribution to this pressing global issue.Next, the article "Autonomous Taxation in Portugal: The Cost of a Tricky Law" by Rita Gigante, Ana Arromba Dinis, and Liliana Pereira, examines autonomous taxation within the Portuguese fiscal system. The study highlights the complexity of tax legislation and the associated costs stemming from disputes in arbitration courts. This work is highly relevant for both professionals and academics in the fields of accounting and taxation, offering valuable insights into the need for simplification and clarity in tax law to improve efficiency and reduce litigation.Our final article, "The Influence of Persuasion on Investor Decision-Making: An Analysis in Light of the Prospect Theory" by Cleber Broietti and Suliani Rover, investigates how persuasion affects investor decision-making within the context of prospect theory. Through an experimental study involving university students, the authors demonstrate how persuasive arguments from financial analysts can mitigate the impact of gains and losses presented in companies’ financial reports, significantly altering the behavior of non-professional investors.We extend our sincere gratitude to all the authors for their valuable contributions and to the reviewers for their diligent and insightful feedback. We are excited about the future of the International Journal of Business Innovation and look forward to bringing you more groundbreaking research in upcoming issues.
Keywords: Editorial